Managerial behavior in fund tournaments—the impact of TrueSkill - Alexander Swade; Gerrit Köchling; Peter N. Posch (Journal of Asset Management, 2021)
Measuring mutual fund managers' skills by Microsoft's TrueSkill algorithm, we find highly skilled managers to behave self-confident resulting in higher risk-taking in the second half of the year compared to less skilled managers. Introducing the TrueSkill algorithm, which is widely used in the e-sports community, to this branch of literature, we can replicate previous findings and theories suggesting overconfidence for mid-years winners.
Keywords: G11; G23; G40; 330; Fund tournament; Skill; Risk-shifting; TrueSkill; Bayesian network